Creating and Evaluating Personas Using Generative AI: A Scoping Review of 81 Articles - Amin, Danial; Salminen, Joni; Ahmed, Farhan; Tervola, Sonja M. H.; Sethi, Sankalp; Jansen, Bernard J. (ACM, 2026)
As generative AI (GenAI) is increasingly applied in persona development to represent real users, understanding the implications and limitations of this technology is essential for establishing robust practices. This scoping review analyzes how 81 articles (2022-2025) use GenAI techniques for the creation, evaluation, and application of personas. The articles exhibited good level of reproducibility, with 61% of articles sharing resources (personas, code, or datasets). Furthermore, conversational persona interfaces are increasingly provided alongside traditional profiles. However, nearly half (45%) of the articles lack evaluation, and the majority (86%) use only GPT models. In some articles, GenAI use creates a risk of circularity, in which the same GenAI model both generates and evaluates outputs. Our findings also suggest that GenAI seems to reduce the role of human developers in the persona-creation process. To mitigate the associated risks, we propose actionable guidelines for the responsible integration of GenAI into persona development.
Keywords: Generative AI; Personas; LLMs; Persona Development; fi=Markkinointi|en=Marketing|; fi=Markkinointi|en=Marketing|; fi=Markkinointi|en=Marketing|